Spondylectomy and lateral lumbar interbody fusion for thoracolumbar kyphosis in an adult with achondroplasia: A case report. Issue 49 (December 2017) - Miyazaki, Masashi; Kanezaki, Shozo; Notani, Naoki; Ishihara, Toshinobu; Tsumura, Hiroshi
Abstract: Rationale: Fixed thoracolumbar kyphosis with spinal stenosis in adult patients with achondroplasia presents a challenging issue. We describe the first case in which spondylectomy and minimally invasive lateral access interbody arthrodesis were used for the treatment of fixed severe thoracolumbar kyphosis and lumbar spinal canal stenosis in an adult with achondroplasia. Patient concerns: A 61-year-old man with a history of achondroplastic dwarfism presented with low back pain and radiculopathy and neurogenic claudication. Diagnoses: Plain radiographs revealed a high-grade thoracolumbar kyphotic deformity with diffuse degenerative changes in the lumbar spine. The apex was located at L2, the local kyphotic angle from L1 to L3 was 105°, and the anterior area was fused from the L1 to L3 vertebrae. MRI revealed significant canal and lateral recess stenosis secondary to facet hypertrophy. Interventions: We planned a front-back correction of the anterior and posterior spinal elements. We first performed anterior release at the fused part from L1 to L3 and XLIF at L3/4 and L4/5. Next, the patient was placed in the prone position. Spondylectomy at the L2 vertebra and posterior fusion from T10 to L5 were performed. Postoperative radiographs revealed L1 to L3 kyphosis of 32°. Outcomes: No complications occurred during or after surgery. Postoperatively, the patient's low back pain and neurological claudication were resolved. No worsening of kyphosis was observed 24 months postoperatively. Lessons: Circumferential decompression of the spinal cord at the apical vertebral level and decompression of lumbar canal stenosis were necessary. Front-back correction of the anterior and posterior spinal elements via spondylectomy and lateral lumbar interbody fusion is a reasonable surgical option for thoracolumbar kyphosis and developmental canal stenosis in patients with achondroplasia.